This place is still beautiful - Tian, XiXi (Young adult author) (Balzer + Bray, an imprint of HarperCollins Publishers, 2022)
"The Flanagan sisters are as different as they come. Seventeen-year-old Annalie is bubbly, sweet, and self-conscious, whereas nineteen-year-old Margaret is sharp and assertive. Margaret looks just like their mother, while Annalie passes for white and looks like the father who abandoned them years ago, leaving their Chinese immigrant mama to raise the girls alone in their small, predominantly white Midwestern town. When their house is vandalized with a shocking racial slur, Margaret rushes home from her summer internship in New York City. She expects outrage. Instead, her sister and mother would rather move on. Especially once Margaret's own investigation begins to make members of their community uncomfortable. For Annalie, this was meant to be a summer of new possibilities, and she resents her sister's sudden presence and insistence on drawing negative attention to their family. Meanwhile Margaret is infuriated with Annalie's passive acceptance of what happened. For Margaret, the summer couldn't possibly get worse, until she crosses paths with someone she swore she'd never see again: her first love, Rajiv Agarwal. As the sisters navigate this unexpected summer, an explosive secret threatens to break apart their relationship, once and for all. This Place Is Still Beautiful is a luminous, captivating story about identity, sisterhood, and how our hometowns are inextricably a part of who we are, even when we outgrow them."--